2015
DOI: 10.1155/2015/643102
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid Attenuates Insulin Resistance via NF-κB to Regulate the IRS1-GLUT4 Pathway in HepG2 Cells

Abstract: The aim of our study is to elucidate the mechanisms of oleanolic acid (OA) on insulin resistance (IR) in HepG2 cells. HepG2 cells were induced with FFA as the insulin resistance model and were treated with OA. Then the glucose content and the levels of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were analyzed. Moreover, protein expression of nuclear factor kappa B (NF-κB), insulin receptor substrate 1(IRS1), and glucose transporter 4 (GLUT4) in cells treated with OA were measured by Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…Recommendations regarding overall diet composition, increased physical activity, weight loss, moderate consumption of alcohol and avoiding tobacco were given identically to both groups. This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Recommendations regarding overall diet composition, increased physical activity, weight loss, moderate consumption of alcohol and avoiding tobacco were given identically to both groups. This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA …”
Section: Discussionsupporting
confidence: 81%
“…This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA. [12][13][14][32][33][34] The PREDIABOLE study also suggests that the long-term administration of a daily dose of 30 mg OA is safe for prediabetic individuals as no adverse effects related to the intervention were either reported during the follow-up or during the two subsequent years. OA has been considered as a very safe over-the-counter drug used for hepatoprotection and for treating hepatitis in China for decades.…”
Section: Safety Of the Dietary Interventionmentioning
confidence: 91%
“…After the low GI reduction diet, we also observed a positive correlation between TNF-α and the level of fasting glucose, suggesting improvement in glucose tolerance after three months of the diet (because of the lack of correlation with glucose concentration 2 h after a meal). Positive correlations between TNF-α and fasting glucose, both before and after the reduction diet, confirm the involvement of this modulator in the development of type II diabetes because of the dysfunction of the insulin receptor and reduced expression of GLUT 4 [35]. However, the results of studies performed among the obese do not confirm a significant role of TNF-α in the development of insulin resistance [12].…”
Section: Correlation Of Tnf-α Before and After Dietary Interventionmentioning
confidence: 99%
“…Overexpression of GLUT4 is a good strategy for treatment of IR [31]. Several natural compounds and medicines such as leanolic acid and liraglutide have been reported to attenuate IR at least partly through increasing GLUT4 expression in liver [32,33]. Previous study showed that black tea polyphenols could promotes GLUT4 translocation in skeletal muscle cells [10].…”
Section: Discussionmentioning
confidence: 99%